Technology, identification, and access to social programs: Experimental evidence from Panama - Angela Reyes; Benjamin Roseth; Diego Alejandro Vera Cossío (Inter-American Development Bank (IDB), 2021)
Access to identification cards (IDs) is often required to claim government benefits. However, it is unclear which policies to increase ID ownership are more effective. We experimentally analyze the effect of two policy interventions to induce the timely renewal of identification cards on access to a government social program in Panama. Sending reminders about expiration dates increased the probability of on-time renewals and of accessing benefits from a social program by 12 and 4.3 percentage points, respectively, relative to a control group. In contrast, allowing individuals to renew their ID online only increased renewals and access to benefits by 8 and 2.9 percentage points, respectively. This result was driven by lower-income individuals. The results suggest that policies to increase ownership of valid identity documentation can reduce inclusion errors in government programs and that simply granting access to digital tools may not be enough to unlock important effects.
Keywords: D90; H53; I38; 330; Digitization; Nudges; Social protection